Safety, Efficacy, and Cost-Effectiveness of Simultaneous Bilateral Arthroscopic Bankart Repair for Bilateral Shoulder Instability. Issue 5 (24th May 2022) - Yildirim, Kerem; Pehlivanoglu, Tuna; Tandogan, Reha N.; Beyzadeoglu, Tahsin
Background: Bilateral shoulder instability and Bankart lesions are not rare and frequently require surgical treatment. Bilateral instability may be treated with either a single-stage, simultaneous bilateral Bankart repair or 2-stage surgery. Purpose/Hypothesis: To compare simultaneous bilateral arthroscopic Bankart repair to 2-stage repair in terms of clinical outcomes and hospitalization costs. It was hypothesized that simultaneous repair would provide clinical outcomes similar to those of 2-stage Bankart repair while yielding lower hospitalization costs. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who underwent simultaneous bilateral arthroscopic Bankart repair (group 1) were matched by age, sex, and injury type to control patients who had unilateral Bankart repair (group 2). All patients were operated on by the same surgeon in the same institution between 2007 and 2017 and had a minimum follow-up duration of 24 months. Patients with inflammatory arthritis, metabolic/malignant disease, previous shoulder surgery, a glenoid bone loss ≥25%, or off-track Hill-Sachs lesion were excluded. The 2 groups were compared in terms of pre- and postoperative Western Ontario Shoulder Instability Index (WOSI) scores, hospitalization costs, complications, and recurrent instability. The hospitalization cost of group 2 was multiplied by 2 to create a projection of the estimated cost of 2 sequential unilateral Bankart repairs. Results: The study population comprised 48 patients (38 men [79.17%] and 10 women [20.83%]; mean age, 25.5 years at surgery and 22.75 years at first dislocation). Group 1 included 32 shoulders in 16 patients, while group 2 consisted of 32 shoulders in 32 patients. The mean hospitalization cost (in 2020 US dollars) was 26, 010 ± 1455 for group 1 and 33, 591 ± 1574 for group 2 ( P < .001). Both groups had improved WOSI scores after surgery and achieved similar scores at the latest follow-up. There was 1 redislocation in each group (3.13%). No surgery- or anesthesia-related/medical complications were recorded in either group. Conclusion: For bilateral shoulder instability, clinical outcomes of simultaneous bilateral arthroscopic Bankart repair were similar to those of 2-stage repair; however, lower hospitalization costs were seen after simultaneous bilateral repair compared with 2-stage surgery.